AB0608 Elevated Circulating Tumor-Associated Antigens in Systemic Sclerosis: Association with Lung Fibrosis. (10th June 2014) - Vacca, A.; Ibba, V.; Cristo, M.; Dessole, G.; Garau, P.; Piga, M.; Porru, G.; Figus, F.; Dessì, M.; Cauli, A.; Mathieu, A.
Abstract : Background: Some tumor-associated antigens (TAAs), apart from cancer cells, are expressed on the surface of inflammatory cells. The production of some TAAs may also be increased in some autoimmune diseases including systemic sclerosis (SSc). Objectives: To assess serum carcinoembryonic antigen (CEA), CA-15.3, CA 125, CA-19.9 levels in SSc patients, and to identify any possible associations with lung involvement parameters. Methods: Eighty-two SSc patients (70 females and 12 males), mean age 64±13 years (range 34-91), disease duration 6±5 years (range 1-27), were consecutively studied. None of the patients ever had any malignancies. Serum TAAs determination were considered and all patients underwent to high-resolution scan (HRCT) and pulmonary function tests (PFTs). CEA, CA 19.9, CA 15.3 and CA125 were determined by electrochemiluminescence immunoassays; the normal upper limit determined by the manufacturer, were as follows: CEA <2.5 ng/ml, CA19.9 <33 U/ml, CA 15.3 <46.5 U/ml, CA125 <21 U/ml. Results: CEA was elevated in 28 (32%) of SSc patients, CA 19.9 in 7 patients (9%), CA 15.3 in 28 patients (36%), CA 125 in 6 patients (8%). Lung fibrosis at HRCT significantly associated with CEA (p<0.0003, r=0.4), CA15.3 (p<0.001, r=0.4), and CA125 (p<0.01, r=0.3) while no association was seen for CA 19.9. Forced vital capacity (FVC) significantly associated only with CA 15.3 (p=0.0001), and diffusion lung capacity for carbon monoxide (DLCO) only with CEA (p=0.04). There was an inverse correlation between CA 15.3, FVC and DLCO (r= -0.52 and r= -0.44, respectively). Conclusions: The production of some TAAs may be elevated in SSc patients; CEA, CA15.3, and CA125 may have a negative prognostic role, being associated with lung fibrosis as documented by HRCT and PFTs. Further studies on higher proportion of patients could be addressed for identifying a surrogate biomarker, among TAAs, for lung involvement in SSc, to assess extent of the disease and possibly with prognostic significance. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5074